The new Harvard guide to women's health - Carlson, Karen J. (Harvard University Press, 2004)
With the publication in 1996 of The Harvard Guide to Women's Health, women seeking answers to questions about their health had access to the combined expertise of physicians from three of the world's most prestigious medical institutions: Harvard Medical School, Massachusetts General Hospital, and Brigham and Women's Hospital. With complete information on women's health concerns, physical and behavioural, this A to Z reference quickly became a definitive resource, praised especially for its coverage of topics not previously considered under the umbrella of women's health. The New Harvard Guide to Women's Health reunites the authors to bring a valued health reference up to date for a new generation and those women who have come to rely on the Harvard Guide. In addition to revised recommendations reflecting the current medical thinking on menopause and hormone replacement therapy, the New Harvard Guide includes: Updated recommendations about cardiac health and heart disease; Entries reflecting recent advances in the understanding and treatment of autoimmune diseases; Better coverage of health concerns throughout a woman's life span, from her first period to menopause and beyond, with a new entry on perimenopause; Expanded nutritional recommendations, including a unique chart of the U.S. government's Daily Reference Intakes for micronutrients, broken down for teens and women whose needs may differ because they are pregnant, breastfeeding, or postmenopausal; Updated information on over-the-counter medications, prescription drugs, procedures, screenings, and diagnostic tests